2006
DOI: 10.1007/s10803-006-0252-5
|View full text |Cite
|
Sign up to set email alerts
|

The ‘Reading the Mind in the Voice’ Test-Revised: A Study of Complex Emotion Recognition in Adults with and Without Autism Spectrum Conditions

Abstract: This study reports a revised version of the 'Reading the Mind in the Voice' (RMV) task. The original task (Rutherford et al., (2002), Journal of Autism and Developmental Disorders, 32, 189-194) suffered from ceiling effects and limited sensitivity. To improve that, the task was shortened and two more foils were added to each of the remaining items. About 50 adults with Asperger Syndrome (AS) or High Functioning Autism (HFA) and 22 matched controls took the revised task. Results show the revised task has good r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
148
3
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(173 citation statements)
references
References 58 publications
(47 reference statements)
15
148
3
7
Order By: Relevance
“…Exploratory analyses of gender differences in the autistic sample yielded significantly higher performance on both direct and indirect tasks of male ASD participants compared to females. Recently, a growing number of studies have reported gender differences within ASD on various behavioral measures including cognitive abilities (Boelte et al 2011;Lai et al 2011;Lord et al 1982) and social cognition in particular (Carter et al 2007;Golan et al , 2007Sucksmith et al 2013). In contrast to our results, previous studies have found higher facial emotion recognition performance in adult females with ASD compared to males Sucksmith et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Exploratory analyses of gender differences in the autistic sample yielded significantly higher performance on both direct and indirect tasks of male ASD participants compared to females. Recently, a growing number of studies have reported gender differences within ASD on various behavioral measures including cognitive abilities (Boelte et al 2011;Lai et al 2011;Lord et al 1982) and social cognition in particular (Carter et al 2007;Golan et al , 2007Sucksmith et al 2013). In contrast to our results, previous studies have found higher facial emotion recognition performance in adult females with ASD compared to males Sucksmith et al 2013).…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our results, previous studies have found higher facial emotion recognition performance in adult females with ASD compared to males Sucksmith et al 2013). However, in line with our results, Carter et al (2007) found that parents reported higher social competences for boys with ASD than for girls and Golan et al (2007) report higher performance on a naturalistic emotional prosody task in autistic males compared to females. Thus, in more complex naturalistic settings, such as inferring mental states from speech and videos, or interacting in real life situations, autistic males seem to have an advantage over females.…”
Section: Discussionsupporting
confidence: 63%
“…Behavioral, psychophysiological, and neuroimaging studies in autism consistently demonstrate deficits in the building blocks for social interaction, such as impaired recognition and memory for facial and vocal expressions (Golan et al, 2006;Humphreys et al, 2007;Paul et al, 2005); reduced use and recognition of emotionally salient aspects of imitation and gesture (Colgan et al, 2006;Hobson & Meyer, 2005); and limited consideration of others' mental states in joint attention or theory of mind tasks (Baron-Cohen et al, 1999;Rutherford et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies in this area have focused primarily on the perception of pragmatic/affective prosody (Chevallier, Noveck, Happé, & Wilson, 2011;Globerson et al, 2014;Golan, Baron-Cohen, & Hill, 2006;Golan, Baron-Cohen, Hill, & Rutherford, 2007;Grossman, Bemis, Plesa Skwerer, & Tager-Flusberg, 2010;Heikkinen et al, 2010;Järvinen-Pasley, Wallace, Ramus, Happé, & Heaton, 2008b;Jones et al, 2011;Kleinman, Marciano, & Ault, 2001;Lindner & Rosén, 2006;Peppé, McCann, Gibbon, O'Hare & Rutherford, 2007;Rutherford, Baron-Cohen, & Wheelwright, 2002). Several of these studies using complex vocal expressions (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…tasks that demand enhanced cognitive load), reported findings for atypical perception of pragmatic and affective prosodic cues in individuals with ASD (e.g., Chevallier et al, 2011;Golan et al, 2006Golan et al, , 2007Kleinman et al, 2001;Rutherford et al, 2002). In contrast, the processing of basic voice expressions and vocalizations (e.g., laughing-happy, crying-sad) appear to be intact in children, adolescents and adults with ASD (Grossman et al, 2010;Heikkinen et al, 2010;Jones et al, 2011), although some studies failed to replicate these findings (Lindner & Rosén, 2006;Mazefsky & Oswald, 2007;Philip et al, 2010).…”
Section: Introductionmentioning
confidence: 99%